Nitrous oxide abuse in a 21-year-old female: a case report and review of literature - Dai, Qi; Chen, Shutong; Zhang, Xiaodan; Fan, Kuixin; Zhang, Jingfeng; Zheng, Jianjun (Frontiers in Neurology, 2024)
The abuse of nitrous oxide (N2O) poses a substantial public health challenge. In many countries, including China, regulations governing the utilization and accessibility to N2O remain ambiguous, particularly within the food industry. Here, we report a case of a 21-year-old female who presented with symptoms of subacute combined degeneration (SCD) of the spinal cord due to N2O abuse. The patient exhibited bilateral lower limb numbness and weakness, low serum vitamin B12 levels with elevated homocysteine levels, and lumbar spine magnetic resonance imaging revealed abnormal signals of the spinal cord. Following cessation of N2O and comprehensive therapy including methylcobalamin and nerve growth factor, the symptoms significantly improved. A follow-up examination three months later showed good progress in gait stability. At a five-year follow-up, the patient's previous clinical symptoms had completely disappeared, and her quality of life had returned to normal. This case underscores the urgency of raising awareness and prevention of N2O abuse, emphasizing the importance of timely diagnosis and comprehensive treatment for patient recovery. Clear formulation and enforcement of relevant regulatory measures are equally crucial in reducing instances of abuse.